Kemampuan Menentukan Unsur Puisi Dengan Berbantuan Media Audio Visual Kelas X SMA Negeri 1 Siberut Selatan - Dwi Muthia Chan; Susanti Marisya; Ria Hillaria Sabolak (JURNAL ARMADA PENDIDIKAN, 2023)
This study focuses on the low poetry writing skills of tenth-grade students at SMA Negeri 1 Siberut Selatan, Mentawai Islands Regency. The purpose of the research is to describe poetry writing abilities with the aid of audio-visual media. The method used is descriptive quantitative research with random sampling techniques. The data analyzed consists of scores from poetry writing tests. The analysis steps include examining students' writings, assessing them based on a rubric, recording scores, determining average scores, and creating histograms. The results show that students' abilities in the theme and message indicators are categorized as "Excellent" with average scores of 91.67 and 89.28, while the imagery indicator is categorized as "Satisfactory" with a score of 54.76. Overall, the poetry writing ability of the students received an average score of 84.92, which falls into the "Excellent" qualification. These results indicate the effectiveness of using audio-visual media in poetry writing instruction.